Risk Factors Predisposing Feline Parvovirus Infection in Feline Population of Chennai - Xavier Mathew; M. Ashokkumar; P. Azhahianambi; A. Ramesh; N. R Senthil (The Indian Veterinary Journal, 2024)
The study analyzed the risk factors predisposing to feline parvovirus (FPV) infection in Chennai. A total of 250 feline faecal DNA samples were screened for FPV with TaqMan RT-qPCR. Risk factors such as temporal distribution, age, sex, breed, type of food, source of drinking water, and contact with stray cats were analyzed using a structured questionnaire. An overall case prevalence of 75.83% was observed in Chennai from January 2022 to May 2023. Risk factors such as period after rainy season, age below six months, nutritionally imbalanced diet, contaminated water sources such as drainage water which is accessible for stray cats and contact with stray cats were found to be the predisposing risk factors of FPV infection.